PARADIGMA NORMATIF KEBERPIHAKAN KEPADA KAUM LAKI-LAKI: Upaya Mewujudkan Kesetaraan Gender dalam Islam - Hasbi Umar (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2019)
This article is to position the gender to its proper and appropiate place. This conducted by criticizing to the interpretation of the holy texts. As the feminism-thinkers are not poles apart in their interpretation, but they are in uniformity and commitment to put back Islam the religion of peace where man is considered equal to each other. Human beings are equal in their efforts to develop their potentials toward their perfection.